The impact of the COVID-19 pandemic on the grief and bereavement of the Eersterust community - Murray, Delene (Department of Public Law, 2025)
Introduction: Strict lockdown regulations during COVID-19 could have led to emotional distress and affected grief. Feelings of distress and guilt can increase when one is unable to care for dying loved ones or get support during changed death rituals. Those that suffer from abnormal grief should be identified and managed promptly. Aim: To explore how COVID-19 lockdown regulations impacted on grieving of public health users of the Eersterust community. Objectives: To determine 1) the incidence of bereavement during the COVID-19 pandemic, 2) the changes in social norms of bereavement, and to 3) explore the individual effects of the changes in norms on members of the community. Methodology: A cross-sectional mixed methods descriptive study was conducted in two phases. Phase 1 consisted of a survey with n=399 health care users, which included the validated pandemic grief scale (PGS). Bereaved individuals from phase 1 participated in phase 2 which consisted of a focus group discussion, individual interviews, and qualitative data derived phase 1 questionnaires. Results: 106 participants (26.6%) experienced loss between 1 March 2020 and 31 August 2021. Significant associations were shown for changes of funerals practices and less support received (p=0.023). The pandemic grief scale (PGS) found a complicated grief incidence of 1.9%, whilst 18.5% of participants expressed counselling needs. Five themes emerged from the qualitative data analysis: Hospitalised loved one, saying goodbye, travel, coping and funerals. Conclusion: The “bereavement curve” was flatter than anticipated, yet lockdown regulations affected the loss experienced. Changes to all aspects of dying, death, and funerals deprived the bereaved from the comforting experiences rituals used to offer. The altered ceremonies left many dissatisfied, although participation was helpful in managing loss. The community's awareness regarding availability of mental health services were poor, but many had received counselling and support from their churches during their bereavement